2009
DOI: 10.1007/s11244-009-9344-8
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Urea in the SCR Process: Combination of DFT Calculations and Experimental Results on the Catalytic Hydrolysis of Isocyanic Acid on TiO2 and Al2O3

Abstract: In selective catalytic reduction (SCR) systems for diesel vehicles the injected urea solution decomposes to ammonia and isocyanic acid (HNCO), which reacts with water to another ammonia molecule and carbon dioxide over the SCR catalyst or a special urea decomposition catalyst. The second reaction step, i.e. the catalytic hydrolysis of HNCO was studied on the anatase TiO 2 (101) surface and Al 2 O 3 (100) surface with ab initio density functional theory (DFT) calculations using a cluster model as well as with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…As a next step the adsorption of isocyanic acid TiO 2 and Al 2 O 3 has been investigated. The calculations revealed that dissociative as well as molecular adsorption of HNCO is possible and energetically feasible on both the TiO 2 (101) [ 6 , 7 ] and the Al 2 O 3 (100) surface [ 8 , 32 , 33 ]. Figure 5 shows adsorption energies as well as geometric structures of HNCO interacting with different sites of TiO 2 (101) and Al 2 O 3 (100).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a next step the adsorption of isocyanic acid TiO 2 and Al 2 O 3 has been investigated. The calculations revealed that dissociative as well as molecular adsorption of HNCO is possible and energetically feasible on both the TiO 2 (101) [ 6 , 7 ] and the Al 2 O 3 (100) surface [ 8 , 32 , 33 ]. Figure 5 shows adsorption energies as well as geometric structures of HNCO interacting with different sites of TiO 2 (101) and Al 2 O 3 (100).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of different catalysts can be used for SCR processes, such as TiO 2 or Al 2 O 3 for the urea decomposition and more complex systems, such as V 2 O 5 /WO 3 -TiO 2 or metal-exchanged zeolites, for the actual SCR reaction. We will exemplarily show the differences in the reaction mechanisms of the hydrolysis of isocyanic acid (HNCO) on anatase TiO 2 (101) and γ-Al 2 O 3 [68], which were revealed combining ab-initio DFT calculations using a cluster model with in situ DRIFTS investigations. Furthermore, a characterization study on the deactivation of V 2 O 5 /WO 3 -TiO 2 SCR catalysts [9] by alkali metals originating from additives or impurities from fuels and lubrication oils has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Czekaj and Kröcher studied the catalytic effect of TiO 2 and c-Al 2 O 3 on HNCO hydrolysis by Diffuse Reflectance Infrared Fourier Transform Spectra (DRIFTS) [38]. e experimental results proved that both TiO 2 and c-Al 2 O 3 had significant catalytic effects on HNCO hydrolysis under the same reaction conditions and TiO 2 had better catalytic performance than c-Al 2 O 3 .…”
Section: Catalytic Hydrolysis Of Hnco During Urea Pyrolysismentioning
confidence: 99%
“…According to their experimental data and calculation results, the activation energy of the HNCO hydrolysis over the two catalysts changed with the temperature range. When the temperature was higher than 200°C, the activation energy of HNCO hydrolysis over c-Al 2 It could be concluded from the analysis of the above literature [33][34][35][36][37][38] that the HNCO hydrolysis over metal oxides catalysts could be basically determined as a reaction process under mass transfer control. However, the determination of whether external or internal mass transfer is still controversial now.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Since HNCO, originating from urea thermolysis, plays a key role in byproduct formation, a catalyst can largely reduce byproduct formation by HNCO hydrolysis [10,11,37]. The best hydrolysis catalyst known for the urea-SCR application is anatase TiO 2 [10,37,[47][48][49]. Also, V 2 O 5 /WO 3 -TiO 2 [13,50] and zeolite-based [10,11,51] SCR catalysts provide high hydrolysis activities.…”
Section: Urea Decomposition Byproducts and Catalyst Deactivationmentioning
confidence: 99%